Analysis of Shopping Activities in E-Commerce among Students and College Students - Nadzwa Safana; Eloh Bahiroh (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
This research aims to analyze e-commerce shopping activities among students and college students, as well as to find out what factors influence e-commerce shopping activities. This research shows what platforms are most chosen by students and college students. This research also shows that e-commerce has benefits for students and college students to find a variety of goods at affordable prices, easier transactions, more energy saving, and ease of comparing prices with other online shops (olshop) businesses.